Improving The Students’ Vocabulary Mastery Through TPR Method At SMP Negeri 29 Medan Tahun Ajaran 2020-2021 - Nirmala Aulia Harahap, Zulfitri (Pusdikra-Publishing.com, 2022)
Vocabulary is one of the essential language components in studying English. Without a propotional amount of vocabulary anyone will get trouble in speaking, reading, listening and writing. In other words, the first that to be master for language learner in learning language especially English is vocabulary. It means that learning vocabulary is very important, especially for students in junior high school. They must master English vocabulary and its grammatical rules to make communicate to another people. A good teaching technique makes students understand and master the lesson like the 2 other lessons which need a suitable technique and methods, teaching language also needs a suitable techniques and methods. In reality learning English especially to memorize vocabulary is boring for some students. One of the method will can improve the students mastery is use TPR (total physical response) in the class. That is way I want to conduct the research with title “Improving the Students’ Vocabulary Mastery Through TPR Method at SMP Negeri 29 Medan Tahun Ajaran 2020-2021’’. This research was conducted at SMP NEGERI 29 MEDAN to be exact in class VIII with a total of 12 students. by using the Classroom action research techniques to get student scores. The results of this study are sought to support the creativity of teachers in teaching and increase knowledge to students about the ease of memorizing vocabulary